Marathon running alters the DNA base excision repair in human skeletal muscle - Radák, Zsolt; Apor, Peter; Pucsok, Jozsef; Berkes, Istvan; Ogonovszky, Helga; Pavlik, Gabor; Nakamoto, Hideko; Goto, Sataro (Life sciences (1973), 2003)
Reactive oxygen and nitrogen species generated either as products of aerobic metabolism or as a consequence of environmental mutagens, oxidatively modify DNA. Formamidopyrimidine-DNA glycosylase (Fpg) and endonuclease III (endo III) or their functional mammalian homologues repair 7,8-dihydro-8-oxoguanine (8-oxoG) and damaged pyrimidines, respectively, to curb the deleterious effects of oxidative DNA alterations. A single bout of physical exercise can induce oxidative DNA damage. However, its effect on the activity of repair enzymes is not known. Here we report that the activity of a functional homolog of Fpg, human 8-oxoG DNA glycosylase (hOGG1), is increased significantly, as measured by the excision of 32P labeled damaged oligonucleotide, in human skeletal muscle after a marathon race. The AP site repair enzyme did not change significantly. Despite the large individual differences among the six subjects measured, data suggest that a single-bout of aerobic exercise increases the activity of hOGG1 which is responsible for the excision of 8-oxoG. The up-regulation of DNA repair enzymes might be an important part of the regular exercise induced adaptation process.